2018
DOI: 10.1515/ncrs-2018-0125
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of caffeinium triiodide – caffeine (1/1), C16H21I3N8O4

Abstract: C16H21I3N8O4, monoclinic, P21/n (no. 14), a = 14.7257(7) Å, b = 10.5712(5) Å, c = 16.7501(8) Å, β = 114.408(2)°, V = 2374.4(2) Å3, Z = 4, Rgt(F) = 0.0254, wRref(F2) = 0.0760, T = 290(2) K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…As a result of the database survey specified above, only a limited number of examples of salt structures containing doubly protonated nicotinium cations have been reported so far [7][8][9][10][11][12]. This contribution is part of our continuing interest in synthesis, characterization and understanding of hydrogen-bonding schemes of salts of natural products [7,[11][12][13][14]. The choice of a [ZnI4] 2− counter anion is part of our general interest in halogen bonding interactions between iodine containing molecules and ions, regardless of whether they are attractive or repulsive [15][16][17].…”
Section: Commentmentioning
confidence: 99%
“…As a result of the database survey specified above, only a limited number of examples of salt structures containing doubly protonated nicotinium cations have been reported so far [7][8][9][10][11][12]. This contribution is part of our continuing interest in synthesis, characterization and understanding of hydrogen-bonding schemes of salts of natural products [7,[11][12][13][14]. The choice of a [ZnI4] 2− counter anion is part of our general interest in halogen bonding interactions between iodine containing molecules and ions, regardless of whether they are attractive or repulsive [15][16][17].…”
Section: Commentmentioning
confidence: 99%
“…We have already shown that heterocyclic cations like pyridinium derivatives [22,23] or naturally occurring bases like caffeine [24] are excellent educts for the synthesis of polyiodide containing salts. In particular, there is profound interest in the competition between hydrogen and halogen bonding in haloanilinium halogenides [25,26].…”
Section: Commentmentioning
confidence: 99%
“…Apart from possible applications there is still an academic interest in the synthesis of new, tailored polyiodides using cationic templates whose lengths and shapes may influence the topology of the polyiodide anions [18][19][20]. We have shown that semi-flexible cations [21][22][23] and heterocyclic cations like pyridinium derivatives [24,25] or naturally occurring base like nicotine [26] or caffeine [27] are excellent tectons for the synthesis of polyiodide containing salts. Many structures with the formal I5 − anion are known [9,19,26], but to the best of our knowledge, only one dimeric cyclic (I5 − ) 2 anion has been reported [28] until now.…”
Section: Commentmentioning
confidence: 99%